From Drug of Choice to Publich Health Tool: A Narrative Review of Ivermectin for Strongyloidiasis Control - Dian Nurmansyah; Lala Gunasari; Puspawati (Indonesian Journal Publisher, 2026)
This narrative review analyses the gap between its clinical supremacy and inadequate public health translation. A structured literature search (2020-2025) using MeSH terms including Ivermectin, Strongyloides stercoralis, and soil-transmitted helminths was conducted via ScienceDirect and Google Scholar. The retrieved evidence synthesizes ivermectin's superior therapeutic profile over albendazole and critically examines the Indonesian context, where significant underdiagnosis and missed opportunities within mass drug administration programs perpetuate transmission. Key implementation barriers spanning diagnostics, policy, and health systems are identified. To address this, the review argues for a strategic paradigm shift: ivermectin must be reenvisioned from a curative agent to a cornerstone of preventative public health. Achieving this requires definitive guideline integration, targeted preventive strategies, and multi-sectoral collaboration